2013
DOI: 10.1007/s11096-012-9745-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Sudanese community pharmacists in public health activities

Abstract: The surveyed community pharmacists favor the provision of public health activities following appropriate training and reduction or removal of barriers. Further interventional studies regarding application of a health education and health promotion model to selected populations in community pharmacies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 17 publications
5
31
2
Order By: Relevance
“…We observed that the attitude towards pharmacist-led smoking cessation services was generally positive as the majority (68.5%) were willing to provide these services in their pharmaceutical practice even though their knowledge of specific tobacco cessation strategies and medication appeared to be somewhat limited, as suggested by the quantitative survey and supported by the FGD findings. This is consistent with findings reported among pharmacists in Cracow, Sudan, Australia and Indonesia, which also showed that community pharmacists were willing to provide smoking cessation services even though some of them had limited knowledge 15,16,18,26 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the attitude towards pharmacist-led smoking cessation services was generally positive as the majority (68.5%) were willing to provide these services in their pharmaceutical practice even though their knowledge of specific tobacco cessation strategies and medication appeared to be somewhat limited, as suggested by the quantitative survey and supported by the FGD findings. This is consistent with findings reported among pharmacists in Cracow, Sudan, Australia and Indonesia, which also showed that community pharmacists were willing to provide smoking cessation services even though some of them had limited knowledge 15,16,18,26 .…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis of the effectiveness of smoking cessation interventions in community pharmacies concluded that pharmacist-led interventions can significantly affect abstinence rates in smokers. [14] Research conducted in other countries like Sudan, Indonesia, Thailand, Poland, U.S.A and Canada report the important role pharmacists may play in smoking cessation [15][16][17][18][19][20] . Studies assessing the role of health professionals in smoking cessation have been carried out among various categories of health care workers, however there is a paucity of data on the pharmacist-led smoking cessation services in Nigeria and other African countries.…”
Section: Introductionmentioning
confidence: 99%
“…showed that interventions incorporating counselling and behavioural change methods by community pharmacists were more effective[27]-a finding that was supported by a scoping review [26]. Evidence from six survey studies indicate that community pharmacists had positive perceptions of their roles in providing smoking cessation services, although self-reported involvement in these activities ranged from 21% in Qatar [28], 39% in the United States [29], 51-71% in Thailand [30], [31], 73% in Turkey [32] and 76% in Sudan [33]. Two studies showed that training [34], and availability, access to and familiarity with smoking cessation guidelines [35] improved community pharmacists' knowledge and involvement in providing smoking cessation services.…”
Section: Smoking Cessation Servicesmentioning
confidence: 99%
“…It provides an important insight into their views and working practices and complements other pharmacy assistant health promotion studies in Australia [15] and Scotland [16] in suggesting such staff have a valuable role. Such views have arguably been under-represented and there has been a tendency to focus on pharmacist perspectives in the public health pharmacy literature [1,4,5] and wider workforce literature. [17,18] This study consolidates several themes from other studies and adds to evidence that there is a perceived need to raise awareness of HLC and HLP much more amongst key stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In particular, the contribution of pharmacies to public health and well-being activities has been emphasised and there is evidence of the effectiveness of some community pharmacy based health promotion services such as coronary heart disease management and prevention and smoking cessation. [2,3] Studies have suggested that pharmacists support engaging more with public health-related roles, in the UK [1] and in countries such as Sudan [4] and Nigeria [5] although additional training needs have been identified. One relatively recent initiative has been the introduction of the Healthy Living Pharmacy (HLP) concept in the UK.…”
Section: Introductionmentioning
confidence: 99%